A moral cartesiana em As Paixões da Alma - Sales, Benes Alencar (2010)
This thesis aims to show that there is a Descartes s moral theory, although he did not leave a particular work on the subject. The Cartesian morality is scattered in his writings, but his last book, The Passions of the Soul, is the one which concentrates most of its contents. To conduct this study, we utilized as a working tool the genetic-historical method, that allowed us to do a genealogical study of the Philosopher's moral, taking as genesis the moral seeds planted in the Cartesian's soil , in the development of the young Descartes, in the Jesuit college of La Flèche. Among the philosophical subjects studied were Aristotle's and Thomas Aquinas' moral. In the study of Latin literature, the students toured works of Cicero and Seneca, in which the rich teachings of the stoic doctrine were present. We also examined the early writings of the Philosopher, left in the form of manuscripts, where there are records of his first thoughts on morals, under the designation of wisdom, forming a group with the sciences. In this genealogical trajectory of his moral, we investigated his first book published, Discourse on Method, in which are the maxims of his provisional morality and the Preface-Letter of the book Principia Philosophiae's french translation, in which Descartes speaks of the highest and most perfect moral system. As a last milestone on the genealogical course traversed, we examined the letters on morals written by the Philosopher to his disciples Princess Elisabeth of Bohemia, Chanut, France's ambassador in Sweden, and Queen Christina of Sweden. It was based on the themes on morals in these letters, deeply studied by Descartes, that was drafted the Traité des Passions (The Passions of the Soul). Without these letters, probably there would be no Traité and we certainly would not speak today of a Cartesian morality. The Cartesian morality is not a preceitual nor a theological one. It is an elevated content moral, a contentment of the mind kind of moral for the man who makes use of his free will, whose acts are the fruit of the agreement established between the intellect and the will. This moral revolves around the virtue of generosity, queen of all virtues, which magnifies the man and make him sympathetic in living with other men. The man in the Cartesian morality recognizes himself as part of the universe and of Earth particularly, that with him make a whole.